Pengaruh Pemberian Komplementer Daun Jambu Biji dan Madu Terhadap Kejadian Diare Pada Balita di Posyandu Mustika Bahari Tahun 2024 - Suhartini, Titin; Ciptiasrini, Uci; Wulandari, Ratna (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Diarrheal disease is one of the infectious diseases of the gastrointestinal tract that is a health problem in the world including Indonesia. Indonesia Health Profile Year 2020 data showed that diarrhea was the number two contributor of deaths in infants aged 29 days–11 months i.e. 9.8% and in the group of toddlers aged 12–59 months accounting for 4.5% of total deaths. This study aims to find out how the influence of complementary administration of guava leaves seeds and honey on the incidence of diarrhea in toddlers in post Mustika Bahari in 2024. The research method uses case study literature review (SCLR) with the number of samples as many as Attack. The results of the study showed that a decrease in the frequency of diarrhea occurred in respondent 1 who was administered the seed jasmine leaf decoction intervention i.e. at the initial visit stool frequency 7x in 24 hours with liquid consistency to 1x in 24 hours with initial solid consistency, as well as in respondent AB visit 2 intervention in honey6 in 24 hours with liquid consistency becomes 2x in 24 hours with tart consistency. The conclusion of the study was that seed guava leaf decoction intervention proved to be more effective in decreasing stool frequency in diarrheic toddlers compared to honey intervention. Advice for mothers of toddlers is expected to be able to apply the education delivered by healthcare workers regarding the administration of decoction of guava seed leaves and honey to children experiencing diarrhea so that diarrheal problems in children can be addressed as soon as possible.